Catalog of gamma-ray glows during four winter seasons in Japan - Y. Wada; T. Matsumoto; T. Enoto; K. Nakazawa; T. Yuasa; Y. Furuta; D. Yonetoku; T. Sawano; G. Okada; H. Nanto; S. Hisadomi; Y. Tsuji; et al. (Physical Review Research, 2021)
In 2015, the Gamma-Ray Observation of Winter Thunderstorms (GROWTH) collaboration launched a mapping observation campaign for high-energy atmospheric phenomena related to thunderstorms and lightning discharges. This campaign has developed a detection network of gamma rays with up to 10 radiation monitors installed in the cities of Kanazawa and Komatsu, Ishikawa Prefecture, Japan, where low-charge-center winter thunderstorms frequently occur. During four winter seasons from October 2016 to April 2020, a total of 70 gamma-ray glows, i.e., minute-lasting bursts of gamma rays originating from thunderclouds, were detected. Their average duration is 58.9 s. Among the detected events, 77% were observed at night. The gamma-ray glows can be classified into temporally symmetric, temporally asymmetric, and lightning-terminated types based on their count-rate histories. An averaged energy spectrum of the gamma-ray glows is well fitted with a power-law function with an exponential cutoff, whose photon index, cutoff energy, and flux are 0.613±0.009 MeV, 4.68±0.04 MeV, and (1.013±0.003)×10^{−5} erg cm^{−2}s^{−1} (0.2–20.0 MeV), respectively. The present paper provides a catalog of gamma-ray glows and their statistical analysis detected during winter thunderstorms in the Kanazawa and Komatsu areas.